An empirical investigation into e-business adoption in the Scottish smaller firm. (11th May 2004) - Wagner, Beverly A.; Fillis, Ian; Johansson, Ulf
The purpose of this research was to investigate e-business adoption and e-supply strategies in Scottish small and medium sized enterprises (SMEs). The paper summarises academic literature on supply chain management, e-commerce drivers and barriers and recent survey reports on the degree of e-business adoption in the UK and Ireland. We then describe the qualitative methodology undertaken, outline findings and discuss the implications from this study to e-supply strategies in the smaller firm. We also examine the role of the support agencies and how government could better serve the SME programmes of assistance. Finally, an outline for future research is presented.